Acute Exercise and Appetite-Regulating Hormones in Overweight and Obese Individuals: A Meta-Analysis - Jessica Anne Douglas; Kevin Deighton; Jan Maria Atkinson; Vahid Sari-Sarraf; David John Stensel; Greg Atkinson (Journal of Obesity)
In lean individuals, acute aerobic exercise is reported to transiently suppress sensations of appetite, suppress blood concentrations of acylated ghrelin (AG), and increase glucagon-like peptide-1 (GLP-1) and peptide-YY (PYY). Findings in overweight/obese individuals have yet to be synthesised. In this systematic review and meta-analysis, we quantified the effects that acute exercise has on AG and total PYY and GLP-1 in overweight/obese individuals. The potential for body mass index (BMI) to act as a moderator for AG was also explored. Six published studies (73 participants, 78% male, mean BMI: 30.6 kg·m−2) met the inclusion criteria. Standardised mean differences (SMDs) and standard errors were extracted for AG and total PYY and GLP-1 concentrations in control and exercise trials and synthesised using a random effects meta-analysis model. BMI was the predictor in metaregression for AG. Exercise moderately suppressed AG area-under-the-curve concentrations (pooled SMD: −0.34, 95% CI: −0.53 to −0.15). The magnitude of this reduction was greater for higher mean BMIs (pooled metaregression slope: −0.04 SMD/kg·m−2 (95% CI: −0.07 to 0.00)). Trivial SMDs were obtained for total PYY (0.10, 95% CI: −0.13 to 0.31) and GLP-1 (−0.03, 95% CI: −0.18 to 0.13). This indicates that exercise in overweight/obese individuals moderately alters AG in a direction that could be associated with decreased hunger and energy intake. This trial is registered with PROSPERO: CRD42014006265.